2000
DOI: 10.1111/j.1752-1688.2000.tb04249.x
|View full text |Cite
|
Sign up to set email alerts
|

ELISA AND GC/MS ANALYSIS OF PESTICIDE RESIDUES IN NORTH CAROLINA1

Abstract: Studies were conducted to analyze the presence of 11 pesticide residues in 12 surface waters in the Piedmont and coastal plain regions of North Carolina. Samples were assayed using enzyme-linked immunosorbent assays (ELISAs). All ELISA results of one part per billion (ppb, pgfL) or greater were confirmed using gas chromatography/mass spectrometry (GCIMS). ELISA detection limits were approximately an order of magnitude higher than GCJMS methods. Of the 5,035 analytical results from 742 surface water samples, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…To meet these requirements in analysis of water samples, HLPC, GC-MS (Grandet et al, 1988;Reupert & Plöger, 1988;Schlett, 1991) and ELISA (Weil et al, 1991;Ben Rejeb et al, 1998;Walker et al, 2000) are established methods providing sufficient sensitivity. Alternatively, biosensors which are compact, low cost devices become increasingly applicable for environmental analysis due to improvements in their sensitivity and stability (Baeumner, 2003;Velasco-Garcia & Mottram, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To meet these requirements in analysis of water samples, HLPC, GC-MS (Grandet et al, 1988;Reupert & Plöger, 1988;Schlett, 1991) and ELISA (Weil et al, 1991;Ben Rejeb et al, 1998;Walker et al, 2000) are established methods providing sufficient sensitivity. Alternatively, biosensors which are compact, low cost devices become increasingly applicable for environmental analysis due to improvements in their sensitivity and stability (Baeumner, 2003;Velasco-Garcia & Mottram, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…9) Several researches have validated inhouse and commercial enzyme-linked immunosorbent assay (ELISA) kits for various pesticides in water. 12,13) Walker et al 14) and Ishii 15) also reported the potential of commercial kits to detect pesticide residue in river water. ELISA results were proven to correlate well with the results from powerful conventional methods such as Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Países da Comunidade Européia adotam como concentração máxima admissível de defensivos, o valor de 0,1 µg/L por composto na água potável (Carney, 1991, Walker et al, 2000. No Brasil, a portaria do Ministério da Saúde, número 1469, de 29 de Dezembro de 2000, que indica os limites máximos de agrotóxicos em água, estabelece para a atrazina o valor máximo aceitável de 2,0 µg/L (Brasil, 2000).…”
Section: Introductionunclassified
“…O emprego de detetores por arranjo de diodos ou por ultravioleta apresenta capacidade para analisar agrotóxicos em concentrações de até 0,1 µg/L (Lee et al, 1983). Vários outros métodos também estão sendo propostos, como uso de ELISA -Enzyme-Linked Immunosorbent Assay (Walker et al, 2000), entre outras derivações (Vink & POLL, 1996;Farran et al, 1999;Houben et al, 1999). Para atrazina foi desenvolvido um método de HPLC (High Performance Liquid Chromatography) seguido de GC-MS (Gas chromatography-Mass Spectrometry) para confirmação da presença do produto (Bagheri et al, 2000).…”
Section: Introductionunclassified